Asynchronous Double Schiff Base Formation of Pyrazole Porous Polymers for Selective Pd Recovery. Issue 8 (2nd March 2021) - Garai, Mousumi; Mahato, Manmatha; Hong, Yeongran; Rozyyev, Vepa; Jeong, Uiseok; Ullah, Zakir; Yavuz, Cafer T.
Abstract: Pyrazole‐linked covalent organic polymer is synthesized using an asynchronous double Schiff base from readily available monomers. The one‐pot reaction features no metals as a building block or reagent, hence facilitating the structural purity and industrial scalability of the design. Through a single‐crystal study on a model compound, the double Schiff base formation is found to follow syn addition, a kinetically favored product, suggesting that reactivity of the amine and carbonyls dictate the order and geometry of the framework building. The highly porous pyrazole polymer COP‐214 is chemically resistant in reactive conditions for over two weeks and thermally stable up to 425 °C in air. COP‐214 shows well‐pronounced gas capture and selectivities, and a high CO2 /N2 selectivity of 102. The strongly coordinating pyrazole sites show rapid uptake and quantitative selectivity of Pd (II) over several coordinating metals (especially Pt (II)) at all pH points that are tested, a remarkably rare feature that is best explained by detailed analysis as the size‐selective strong coordination of Pd onto pyrazoles. Density functional theory (DFT) calculations show energetically favorable Pd binding between the metal and N‐sites of COP‐214. The polymer is reusable multiple times without loss of activity, providing great incentives for an industrial prospect. Abstract : One step, consequential imine linking produced the first pyrazole network polymers with an unusual selectivity for the syn addition. Proven by single‐crystal studies, a kinetic controlled product provides tailor‐made pockets for rapid, pH independent, reversible Pd binding and an exceptional selectivity over other strongly coordinating precious metals like platinum.